Evaluación de tres niveles de fertilización orgánica, (compost) con tres densidades de siembra en el cultivo de papa variedad INIAP puca shungo (solanum andígena). con tecnología limpia, en la parroquia Pastocalle, Latacunga, Cotopaxi. 2013 - Espinoza Angulo, Martin Olmedo (2015)
The research theme was "EVALUATION OF THREE LEVELS OF ORGANIC FERTILIZER (COMPOST) THREE PLANTING DENSITIES IN VARIETY INIAPPUCA potato Puca Shungo (Solanum andígena). WITH CLEAN TECHNOLOGY IN THE PARISH Pastocalle, LATACUNGA, Cotopaxi. 2013. "The theme was chosen in a native potato that currently is not well known and secondly organic fertilization to produce a potato that does not affect the health of consumers. The specific objectives were: To know the most appropriate level of organic fertilizer for the production of potato cultivation INIAP Puca shungo identify optimal planting density for the production of potato cultivation INIAP puca shungo and economically analyze treatments. Two factors, the first levels of organic fertilization and the second factor densities were studied. Designing randomized complete block factorial arrangement was applied axb + 1 with 10 treatments and 4 replications. For the interpretation of the results Analysis of Variance and Tukey test at 5% for sources of variation were significant at 1% was applied. The variables evaluated were: days to germination, number of stems per plant, stem diameter, plant height, incidence and severity of illness, days to flowering, days to harvest….